Connecting deliberative mini-publics to representative decision making - Setälä Maija (Wiley, 2022)
Despite some prominent critics, deliberative democrats tend to be optimistic about the potential
of deliberative mini-publics. However, the problem with current practices is that mini-publics are typically
used by officials on an ad hoc basis and that their policy impacts remain vague. Mini-publics seem
especially hard to integrate into representative decision making. There are a number of reasons for
this, especially prevailing ideas of representation and accountability as well as the contestatory character
of representative politics. This article argues that deliberative mini-publics should be regarded as one
possible way of improving the epistemic quality of representative decision making and explores different
institutional designs through which deliberative mini-publics could be better integrated into representative
institutions. The article considers arrangements which institutionalise the use of mini-publics; involve
representatives in deliberations; motivate public interactions between mini-publics and representatives;
and provide opportunities to ex post scrutiny or suspensive veto powers for mini-publics. The article
analyses prospects and problems of these measures, and considers their applicability in different contexts of
representative politics.